Postural change-dependent T-wave oversensing resulting in the administration of inappropriate shocks - Yukoh Hirai; Yukiko Nakano; Hiroshi Ogi; Yasuki Kihara (Journal of Arrhythmia, 2012)
A 68-year-old man with dilated cardiomyopathy (left ventricular ejection fraction, 15%) and nonsustained ventricular tachycardia received an implantable cardioverter defibrillator. Even though his cardiac status had greatly improved 2 years later after β-blocker therapy, he experienced 2 episodes of sudden shock when he was squatting in a bathroom without any preceding symptoms. His serum electrolyte and plasma glucose levels were normal. Interrogation of the device revealed that the shock was caused by sinus tachycardia and T-wave oversensing. A number of episodes of nonsustained ventricular tachycardia due to T-wave oversensing was also recorded. Follow-up interrogation of the device with the patient in the supine position could not reproduce the T-wave oversensing. We were able to elicit T-wave oversensing only after reproduction of the patient's clinical situation using isoproterenol and postural changes (i.e., sinus tachycardia and squatting). This case suggests that sudden increases in nonsustained ventricular tachycardia events may be caused by T-wave oversensing, and postural changes should be taken into consideration in such situations.